2022
DOI: 10.1108/qrfm-07-2021-0118
|View full text |Cite
|
Sign up to set email alerts
|

Does Tawarruq still remain the top option for Islamic home financing (IHF) products in Malaysia?

Abstract: Purpose The purpose of this study is to investigate whether Tawarruq Islamic home financing (IHF) products remain untouched and maintain their position as the top IHF product in Malaysia. Design/methodology/approach The study adopted a qualitative research methodology that included both literature review and content analysis. Firstly, the existing studies and literature were reviewed to compare different types of IHF. The composition of IHF products offered by these Islamic banks was then investigated furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
6
0
3
Order By: Relevance
“…According to Maqasid al-Shariah, the findings are criteria that tend to gauge the performance of Islamic banks. Specifically, Ibrahim and Mohd Sapian (2022) highlighted research on the influence of customer preferences on house financing decisions and their enthusiasm for Islamic banking products. Minaryanti and Mihajat (2023) conducted a detailed research analysis on the relationship between Sharia governance from the Sharia Supervisory Board and internal Sharia compliance, as well as its effect on the performance of Islamic banks.…”
Section: Jima 154mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Maqasid al-Shariah, the findings are criteria that tend to gauge the performance of Islamic banks. Specifically, Ibrahim and Mohd Sapian (2022) highlighted research on the influence of customer preferences on house financing decisions and their enthusiasm for Islamic banking products. Minaryanti and Mihajat (2023) conducted a detailed research analysis on the relationship between Sharia governance from the Sharia Supervisory Board and internal Sharia compliance, as well as its effect on the performance of Islamic banks.…”
Section: Jima 154mentioning
confidence: 99%
“…Several research studies have examined customer views and attitudes toward Islamic banking products and identified the factors influencing consumer compliance with Islamic standards (Shah et al , 2023). Another study has explored the characteristics that influence customer selection of Islamic banking services, focusing on the Sharia compliance behaviour of bank customers (Ibrahim and Mohd Sapian, 2022). Additionally, previous authors explore the elements that influence the selection of Islamic banking services, shedding light on Islamic client behaviour (Hoque et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu bakış açısıyla teverruk, İslama uygun olmayan muameleler için kanunu dolanma olarak nitelendirilmektedir. Bu yönüyle karşı çıkanlara ek olarak borca dayalı yöntemlerin piyasada baskın olmasının önüne geçmekte fayda olduğu yönünde görüşler de mevcuttur [5].…”
Section: Organize Teverrukunclassified
“…Bu önemli bir özelliktir. LME'de bakır, nikel, alüminyum, çinko, kurşun gibi metallerin yanı sıra platin, altın, gümüş, paladyum gibi değerli metallerin de ticareti yapılmaktadır [5].…”
Section: Londra Metal Borsası (London Metalunclassified
See 1 more Smart Citation